2019
DOI: 10.1007/s10522-019-09846-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of curcumin on replicative and chronological aging in the Saccharomyces cerevisiae yeast

Abstract: Curcumin is a biologically active compound of vegetable origin which has a hormetic effect. Pro-health and anti-aging properties of curcumin have been known for years. The main benefit of curcumin is thought to be its anti-oxidative action. Despite vast amount of data confirming age-delaying activity of curcumin in various groups of organisms, so far little has been discovered about curcumin's impact on cell aging in the experimental model of the Saccharomyces cerevisiae budding yeast. We have been able to dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 46 publications
(63 reference statements)
4
16
0
Order By: Relevance
“…These antiaging qualities possessed by antioxidant-rich PLME extract from P. longifolia leaf might contribute to extending the RLS of PLME-treated S. cerevisiae BY611 yeast cells, as observed in this study. Similar findings were also reported by Stępień et al (2020) on curcumin, a vegetable-origin bioactive compound that delays replicative aging of the S. cerevisiae wild-type strain BY4741. Indeed, the RLS reported in this study echoes the reproduction potential of S. cerevisiae BY611 yeast cells, but not the actual longevity of the yeast cells studied.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These antiaging qualities possessed by antioxidant-rich PLME extract from P. longifolia leaf might contribute to extending the RLS of PLME-treated S. cerevisiae BY611 yeast cells, as observed in this study. Similar findings were also reported by Stępień et al (2020) on curcumin, a vegetable-origin bioactive compound that delays replicative aging of the S. cerevisiae wild-type strain BY4741. Indeed, the RLS reported in this study echoes the reproduction potential of S. cerevisiae BY611 yeast cells, but not the actual longevity of the yeast cells studied.…”
Section: Discussionsupporting
confidence: 89%
“…As seen in Figure 1, PLME treatment positively impacted the RLS of S. cerevisiae BY611 yeast cells. The number of daughter cells formed by the mother yeast cell before the cell cycle terminates irreversibly is portrayed as the measurement of life of the yeast cell in the RLS study in a yeast model (Stępień et al, 2020). The quantification of the number of daughter yeast cells formed by a mother yeast cell was done with the aid of a microscope equipped with a micromanipulator to physically separate the daughter cells (Kaeberlein, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The total lifespan of the yeast cultures was determined as previously described [ 29 ] with small modifications [ 30 ]. Then, 10 μL aliquots of a fresh yeast culture were collected and transferred to YPD plates with Phloxine B (Fisher Scientific Company, Montreal, QC, Canada) (10 μg/mL) in the medium.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of the produced reactive oxygen species (superoxide anion) was assessed with dihydroethidium (hydroethidine, DHET; final concentration 18.9 μM) (Invitrogen, ThermoFisher Scientific, Waltham, MA USA), as described previously [ 30 ]. Exponentially growing yeast cells were washed with sterile water and diluted to the final density of 10 8 cells/mL in 100 mM phosphate buffer pH 7.0 containing 0.1% ( w / v ) glucose and 1 mM sodium EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic and metabolic engineering approaches identified factors that delay the onset of aging and cell death in many model species (Stępień et al 2020 ; Gómez-Linton et al 2019 ). Early studies revealed the Sirtuins and TOR (Target of Rapamycin) signaling as longevity regulators (Longo and Kennedy 2006 ; Powers et al 2006 ; Wierman and Smith 2014 ).…”
Section: Introductionmentioning
confidence: 99%